Modeling a multiple-chain emeraldine gas sensor for NH3 and NO2 detection - Sustkova, Hana; Voves, Jan (Beilstein Journal of Nanotechnology, 2022)
This paper describes atomistic device models of a multiple-chain polyaniline (PANI) gas sensing component, utilizing the non-equilibrium Green’s functions formalism. The numerical results are compared with experimental data of ammonia and nitrogen dioxide detection. Multiple molecules of PANI in the form of emeraldine salt were studied with more than one absorbed molecule of ammonia or nitrogen dioxide. From the I–V characteristics of the system with and without adsorbed gas molecules for gas concentrations of 3, 6, 9, and 12 ppm, the effective resistance changes, (R − R0)/R0, were obtained and compared with experimental results. A good agreement with the measured values was obtained. In summary, PANI as emeraldine salt was numerically modeled for several adsorbed gas concentrations, several gas configurations, and different PANI molecule positions, including carrier hopping between them. The results are comparable to the experiment and show good properties for the application as gas sensor device for NH3 detection and rather good properties for NO2 detection.
Keywords: ammonia; gas sensor; nitrogen dioxide; numerical computation; polyaniline